2016
DOI: 10.5812/jjm.30708
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Neoteric Serotypes Among Multidrug Resistant Strains of Streptococcus pneumoniae Prevalent in Egypt

Abstract: BackgroundStreptococcus pneumoniae is still one of the major causes of morbidity and mortality worldwide. The prevalent serotype distribution had shown variation along different studies conducted at different time intervals. In order to efficiently assess the epidemiology of the diseases for effective preventive and treatment strategies, serotype prevalence need to be periodically reassessed.ObjectivesConducting a reassessment of the prevalent S. pneumoniae serotypes in Egypt as an essential step in the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Isolates were cultured and identified as S. pneumoniae , the serotyping of which revealed that the most common serotypes are 6A/B (30%) followed by 19F (28%), (Table 1) (Bahy et al, 2016). Consequently, the serotypes 6A/B and 19F were considered as the most predominant serotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates were cultured and identified as S. pneumoniae , the serotyping of which revealed that the most common serotypes are 6A/B (30%) followed by 19F (28%), (Table 1) (Bahy et al, 2016). Consequently, the serotypes 6A/B and 19F were considered as the most predominant serotypes.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, it was found that currently the most predominant serotypes in Egypt are serotypes 6A/B and 19F of invasive S. pneumoniae which also showed alarming levels of multi drug resistance (Bahy et al, 2016). Both serotypes all together accounted for over 50% of the prevalent types.…”
Section: Introductionmentioning
confidence: 99%
“…The consistency of the ndings described with those available in the literature on speci c pathogens in the region leads to hypothesize that, despite the limitations above described, the concerning high proportion of AMR strains detected in this review has a certain degree of validity. * Articles can report antibiotic resistance profile on more than one pathogen, and therefore the sum of the articles in this table can differ from the total per Country detailed * Articles can report antibiotic resistance profile on more than one pathogen, and therefore the sum of the articles in this table can differ from the total per Country detailed ¶ Articles can describe results for more than one Country: in such case they are counted only once in the total (46,60,67,76,83,93,120,121,139,148,171)…”
Section: Limitationsmentioning
confidence: 99%
“…Mutations of GtfA, including N98A, E244A, E332A and S403A, block the glycosylation of PsrP (2,10). To date, 94 S. pneumoniae serotypes have been found (11)(12)(13)(14). Previous studies showed that PsrP was only detected in 51.7% of invasive S. pneumoniae isolates and in 48.3% of carrier S. pneumoniae isolates (15), thus, we sought to examine if the presence of the PsrP-SecY2A2 island is associated to a certain serotype of S. pneumoniae, or if GtfA and GtfB are conserved among these S. pneumoniae isolates and involved in the glycosylation of PsrP via the formation of the glycosyltransferase complex GtfA-GtfB.…”
Section: Introductionmentioning
confidence: 99%